1981
DOI: 10.1007/bf01890253
|View full text |Cite
|
Sign up to set email alerts
|

Strongyloides stercoralis hyperinfection: Sequential changes of gastrointestinal radiology after treatment with thiabendazole

Abstract: Sequential changes of gastrointestinal radiology are described in a case of Strongyloides stercoralis hyperinfection. Duodenal dilatation, reflux of barium into the biliary and pancreatic duct, and mucosal thickening of the small intestine were the striking features before treatment. Although treatment with thiabendazole led to rapid and complete clearance of rhabditiform larvae, some abnormal radiologic changes in the small intestine persisted for approximately 4 months before the mucosal pattern reverted to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1983
1983
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Jaundice owing to reflex spasm of the sphincter of Oddi that is caused by S. stercoralis infection is rare, and it can also occur in Crohn's disease (12). Yoshida et al reported a unique case of a patient with S. stercoralis hyperinfection who showed regurgitation of the contrast medium into the biliary and pancreatic duct in a barium meal study (13). Reports on papillary obstruction in jaundice due to S. stercoralis infection are very rare.…”
Section: Discussionmentioning
confidence: 99%
“…Jaundice owing to reflex spasm of the sphincter of Oddi that is caused by S. stercoralis infection is rare, and it can also occur in Crohn's disease (12). Yoshida et al reported a unique case of a patient with S. stercoralis hyperinfection who showed regurgitation of the contrast medium into the biliary and pancreatic duct in a barium meal study (13). Reports on papillary obstruction in jaundice due to S. stercoralis infection are very rare.…”
Section: Discussionmentioning
confidence: 99%
“…S. stercoralis is mainly found in the duodenum, including the duodenal papilla, where the larvae mature into adult female parasites and induce varied patterns of inflammatory reactions. Biliary manifestations of strongyloidiasis are rare; however, some reports have described mechanical obstruction of the duodenal papilla and involvement of the bile ducts secondary to strongyloidiasis (Hokama et al 1998;Delarocque Astagneau et al 1994;Hennequin et al 1991;Dearden et al 2004;Penalba et al 1983;Yoshida et al 1981). In the present study, S. stercoralis larvae in the bile were found in one case.…”
Section: Discussionmentioning
confidence: 96%
“…Changes in host-parasite relationship, especially in older patients, convert the chronic asymptomatic parasitosis into a debilitating and even lethal infection. In addition, patients who are on immunosuppressive therapy and steroids are likely to develop clinical evidence of the infestation [1,4].…”
mentioning
confidence: 99%